Inovasi media dakwah Pimpinan Ranting Muhammadiyah Desa Suko Kec. Sidoarjo melalui Taman Baca digital (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Management of Reading Gardens for Muhammadiyah Branch Leaders in Suko Village, Kec. Sidoarjo Kab. Sidoarjo, East Java, during the last few years experienced a significant decline, this was due to a number of things, including the management system for reading gardens was still carried out traditionally, while in this pandemic condition, the impact was that reading gardens were often closed which caused them to appear poorly maintained so many residents who cannot use the reading garden to gain knowledge. With these problems, the solutions offered are improving services and improving/assisting service facilities by modernizing the Taman Baca management system by digitizing the Reading Gardens. So that by modernizing the management of the Reading Gardens and doing it professionally, it can maximize the potential of the Reading Gardens of the Muhammadiyah Branch Leadership in Suko village, sub-district. Sidoarjo kab. Sidoarjo, East Java, as well as being able to provide a stimulus in an effort to increase the love of reading and professionalism of management and administrators. The method of implementing this activity is carried out with several approaches, namely Participatory Rural Appraisal and Participatory Technology Development. The implementation technique is divided into 3 (three) stages, namely preparation, implementation and evaluation monitoring. so that the end result of the modernization of this Reading Park is to make the PRM Reading Garden in Suko village a sub-district. Sidoarjo, becomes a reference for independent public libraries in Sidoarjo, especially for similar reading parks managed by PRM throughout East Java and improves thinking, reading and writing skills or other skills needed (soft skills and hard skills) by the community.